Evaluation of recombinant yeast strains expressing a xylanase, amylase or an endo-glucanase in brewing - Makuru, Moshabane Phillip (My University, 2018)
Beer is one of the most widely consumed alcoholic beverages in the world. The brewing process is based on natural enzymatic activities that take place during the malting of barley grain, mashing of grist and fermentation of wort. Insufficient malt enzyme activity during the mashing process leads to high levels of barley β-glucan, arabinoxylan (AX) and dextrins in the wort as well as in the final beer. It was reported that high levels of β-glucan and AX increase wort and beer viscosity which lower the rate of beer filtration and this negatively affect the production rate in the brewery. During beer fermentation, brewing yeast catalyses the conversion of wort sugars to ethanol, carbon dioxide and other metabolic products. However, non-fermentable carbohydrates i.e., limit dextrins remain in the wort and final beer. These non-fermentable carbohydrates are known to contribute to the caloric value of beer which might lead to weight gain in consumers. The objectives of this study were to evaluate the effect of recombinant yeast strains expressing an endo-β-1,4-glucanase or an endo-β-1,4-xylanase on beer viscosity (as an indicator of filterability) and an α-amylase on residual sugars levels. The effect of the above mentioned enzymes on the aroma, appearance, flavour, mouth-feel and overall quality of the beer was also determined. Wort was produced in the University of Limpopo micro-brewery and the wort was pitched with different recombinant strains. The wild-type strain served as control. The results obtained showed that the xylanase expressing strain produced a measurable decrease in viscosity over the course of the fermentation, but endo-glucanase did not have any effect on the beer viscosity. The α-amylase producing strain, did not show a measurable reduction of residual sugars in the final beer probably as a result of very low activity on α-1,6 glycosidic bonds in dextrins during fermentation. The xylanase and α-amylase producing strain fermented effectively with good attenuation (decrease in wort specific gravity). The beer produced by the α-amylase and control strains were preferred in terms of taste and had similar qualities. The secreted amylolytic activity was not sufficient to significantly reduce residual sugar in the final beer. Although the xylanase secreting strain produced a beer with lower viscosity, the enzyme had a negative impact on the taste of the beer. Key words: Brewer’s yeast, beer fermentation, low calorie beer, amylase, xylanase, endo-glucanase.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2018
Keywords: Beer; Yeast strains; Xylanase; Amylase; Brewers yeast; Beer fermentation; low calorie beer; Brewing; Flavored alcoholic beverages; Yeast fungi -- Biotechnology -- Congresses; Enzymes -- Biotechnology -- Congresses